Clinical profile, treatment, and outcomes of febrile neutropenia in hematologic disorders: a look at 30-day mortality predictors - Eskedar Ferdu Azerefegne; Gebeyehu Tessema Azibte; Fitsum Seyoum Bekele; Kehabtimer Shiferaw Kotiso; Berhanu Moges Abera; Bereket Abraha Molla; Yonatan Habtamu Tamene; Wondwossen Amogne Degu (Scientific Reports)
Abstract Patients with hematologic malignancies are susceptible to neutropenic fever, a potentially life-threatening condition. This study investigated the association between clinical profiles, treatment, and outcomes in these patients. A retrospective analysis of 132 patients with first-time neutropenic fever and hematologic malignancy diagnosed at Tikur Anbessa Specialized Hospital, Ethiopia, between 2019-01-01 and 2019-12-31 was conducted. Data on demographics, underlying malignancy, presumed infection site, treatment, and 30-day mortality were collected. ale predominance (13:10) was observed. Acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) were the most common malignancies (43.2% and 40.9%, respectively). Chest focus of infection was the most frequent primary source (33%). Cefepime and Vancomycin combination therapy was used in 40.9% of patients. Prior febrile neutropenia and medical ICU admission during treatment significantly increased the odds of 30-day mortality (adjusted odds ratio 3.8 and 5.4, respectively). This study highlights the crucial role of prior febrile neutropenia and medical ICU admission in predicting mortality within 30 days of neutropenic fever diagnosis in patients with hematologic malignancies.